Animasi Interaktif Dua Dimensi Pedoman Gizi Seimbang - Jerwin, Langie J.F.; Lumenta, Arie S. M.; Sugiarso, Brave A. (Jurnal Teknik Informatika, 2020)
Abstrack—Indonesia is a developing country. To be a developed country One of them has a nation that has a high level of health, intelligence and productivity. The third thing is nutrition policy. Diet is the most important. Along with developments in the world of health, eating pattern 4 healthy 5 perfect has been replaced by the Guidelines for Balanced Nutrition. 2-dimensional interactive animation Guidelines for Balanced Nutrition to support the importance of nutrition for health through animated videos. This animation was built using a Life Cycle Development research methodology that has 6 stages, concepts, design, material collection, assembly, testing, and distribution using Work Breakdown Structure work collaboration to be more structured. The conclusion is this 2-dimensional Animation of the Balanced Nutrition Guidelines is one of the most useful and helpful media in the guidelines on Balanced Nutrition Guidelines. From these results it can be concluded that 100% of respondents answered with positive responses.       Keywords—Video, balanced nutrition guidelines, interactive animation, MDLC, WBS.  Abstrak—Indonesia merupakan negara yang berkembang. Untuk menjadi negara maju salah satunya adalah mempunyai bangsa yang memiliki tingkat kesehatan, kecerdasan, dan produktifitas yang tinggi. Ketiga hal ini dipengaruhi oleh keadaan gizi. Pola makan merupakan perilaku paling penting yang dapat mempengaruhi keadaan gizi. Seiring dengan perkembangan di dunia kesehatan, pola makan 4 sehat 5 sempurna sudah digantikan oleh Pedoman Gizi Seimbang. Animasi interaktif  2 dimensi Pedoman Gizi Seimbang bertujuan untuk memperkenalkan pentingnya gizi bagi kesehatan tubuh melalui video animasi. Animasi ini dibangun menggunakan Metodologi penilitian Development Life Cycle yang memiliki 6 tahapan, concept, design, material collecting, assembly, testing, dan distribution dengan menggunakan kerangka kerja Work Breakdown Sctructure agar lebih terstruktur. Kesimpulannya adalah Animasi 2 dimensi Pedoman Gizi Seimbang ini menjadi salah satu media pengenalan yang sangat bermanfaat dan membantu dalam mempelajari tentang Pedoman Gizi Seimbang. Dari hasil tersebut bisa diambil kesimpulan bahwa 100% responden menjawab dengan tanggapan positif. Kata kunci—Video, Pedoman Gizi Seimbang, Animasi Interaktif, MDLC, WBS.